Smoke plumes from wildfires and the electrical state of the surface air layer - Nagorskiy, Petr M. (Atmospheric and oceanic optics)
Using ground-based observation and satellite remote sensing data from 2006 to 2020 the smoke effect from distant wildfires in Siberia on the electrical state of the surface air layer is studied. The cases are considered where smoke covers the troposphere down to the surface layer and where smoke is observed only in the middle and upper troposphere. It is found that smoke from wildfires in these cases strongly but differently affects the electrical state of the surface air layer.